A Very Rare Benign Giant Osteoma in Tempero-parieto-occipital Region (Bangladesh Journal of Neurosurgery, 2020)
Osteoma is a slow growing benign mesenchymalosteoblastic tumor formed by maturebone tissue. The most common site reported is the fronto-ethmoidal region andneighboring sinuses.Involvement of the temporal and occipital squama is extremelyrare. Like giant osteomas in other locations of the skull, they can reach large volumesbut are essentially benign and potentially curable by excision.The author present acase of giant osteoma in Temporo-Parieto-Occipital region in a teenage girl.Bang. J Neurosurgery 2020; 9(2): 173-177